Protein Kinase C-Mediated Hyperphosphorylation and Lateralization of Connexin 43 Are Involved in Autoimmune Myocarditis-Induced Prolongation of QRS Complex - Zhong, Chunlian; Zhao, Huan; Xie, Xinwen; Qi, Zhi; Li, Yumei; Jia, Lee; Zhang, Jinwei; Lu, Yusheng (Frontiers in Physiology, 2022)
Myocarditis is a serious and potentially life-threatening disease, leading to cardiac dysfunction and sudden cardiac death. Growing evidence suggests that myocarditis is also a malignant complication of coronavirus pneumonia, associated with heart failure and sudden cardiac death. Prolonged QRS complexes related to malignant arrhythmias caused by myocarditis significantly increase the risk of sudden cardiac death in patients. However, the molecular mechanisms are not fully known at present. In the present study, we identify protein kinase C (PKC) as a new regulator of the QRS complex. In isolated hearts of normal rats, the PKC agonist phorbol-12-myristate-13-acetate (PMA) induced prolongation of the QRS complex. Mechanistically, hyperphosphorylation and lateralization of connexin 43 (Cx43) by PKC induced depolymerization and internalization of Cx43 gap junction channels and prolongation of the QRS duration. Conversely, administration of the PKC inhibitor, Ro-32-0432, in experimental autoimmune myocarditis (EAM) rat after the most severe inflammation period still significantly rescued the stability of the Cx43 gap junction and alleviated prolongation of the QRS complex. Ro-32-0432 reduced phosphorylation and blocked translocation of Cx43 in EAM rat heart but did not regulate the mRNA expression level of ventricular ion channels and the other regulatory proteins, indicating that inhibition of PKC might have no protective effect on ion channels generating ventricular action potential in EAM rats. These results suggest that pharmacological inhibition of PKC ameliorates the prolongation of the QRS complex via suppression of Cx43 hyperphosphorylation, lateralization, and depolymerization of Cx43 gap junction channels in EAM rats, providing a potential therapeutic strategy for myocarditis-induced arrhythmias.